Association of Foetal Haemoglobin with Pancreatic Enzymes in Sickle Cell Disease Patients in Benin City, Nigeria - Emokpae MA; Ehioghae I; Onaiwu MO (International Journal of Medical Research, 2015)
Background & Objective: There are conflicting reports on the potential protective effects of foetal haemoglobin (HbF) in the elimination of symptoms of Sickle cell disease in the patients and reports which correlate the levels of HbF with pancreatic enzymes in SCD are scare in the literature. This study correlates the levels of HbF on pancreatic enzymes activities in SCD patients on steady clinical state. Materials and Methods: Serum amylase and lipase as well as urine amylase were determined using commercially available reagents kits. Control sera were included in all assays to ensure accuracy and precision of the analytes. Student’s t-test was used to compared data at 95% confidence intervals (p<0.05) and Pearson correlation coefficient was used to calculate the association of HbF with measured variables. Results: Urine amylase (p=0.01), serum amylase (p<0.001) and lipase (p=0.002) were significantly decrease in sickle cell patients with high (>5%) HbF when compared to those with low (<4.9%) HbF. Foetal haemoglobin levels correlated negatively with serum lipase (r ) and amylase (r ) but the correlation with urine amylase (r ) was not however significant. Conclusion: SCD patients with lower HbF were characterized with higher levels of pancreatic enzymes than those higher HbF levels; hence SCD patients subjects with lower HbF are more predisposed to chronic pancreatitis. It would be interesting to repeat the study in SCD patients with abdominal pain in other to reveal the overall involvement of the pancreas in the disease process.